Narrative Review: The Potential Of Morus Alba And Morus Nigra As Anti-Inflammatory And Antioxidant - Indawati, Iin; Kintoko (Ann Publisher, 2024)
Introduction: Oxidative stress causes various diseases. Inflammation is the body's response to tissue infections and injuries. Mulberry is a multifunctional plant with bioactive components that have potent antioxidant and anti-inflammatory activities. This study aims to determine the activity of antioxidants, anti-inflations, extraction processes, active compounds, and methods used for antioxidant and anti-inflammatory testing. Methods: Narrative review using a literature search using Google Scholar and PubMed. Results: The results of Morus alba and Morus nigra have antioxidant activity, the plant parts used by leaves, fruits, and roots. Various methods were used to determine antioxidant activity, including DPPH, reducing power assay, β-carotene bleaching, and Hydroxyl radical scavenger capacity. Conclusion: Anti-inflammatory mechanism of mulberry bioactive compounds by inhibiting several cytokines and inflammatory mediators such as IL-1β, IL-6, IL-8, IL-9, IL-10, IL-23a, IFN-ɣ, TNF-ɑ, MMP-3, MMP-9, TLR, COX-2, NF-kB and iNOS. Testing of antioxidant activity by DPPH, ABTS, FRAP, reducing power assay, β-carotene bleaching, and Hydroxyl radical scavenger capacity